Discovery and development of biological agents to control crop pests - Slininger,Patricia J. (2003)
Thousands of potential microbial biocontrol agents have been isolated from agricultural fields and crops during research over the last 80 years, yet only a few are in commercial use. Recently, public health and safety concerns about the environmental impact of chemical pesticides have led to consideration of biological control as a natural approach to maintaining crop health. Despite environmental incentives and strong research efforts, commercialization of biocontrol agents has been slow to evolve. The momentum of the chemical industry is difficult to shift, and fermentation processes tend to be more expensive to operate than synthetic chemical processes.Yet there is a demand for biological control products, especially in agricultural niche markets, where there is no chemical competitor. However, given this market demand, the fundamental methods of economical large-scale production and application of biological control agents are lacking. Many aspects of biocontrol agent production and development represent untrodden territory in the progression of industrial fermentation technology beyond its well-established food and pharmaceuticals niche. Distinguishing them from traditional fermentation products, biocontrol agents must not only be produced in high yield but must also meet the following quality criteria: high (near 100%) retention of cell viability with maintenance of crop compatibility and consistent bioefficacy during several months of storage. Research examples will be reviewed to illustrate the challenges and strategies of developing processes to manufacture and deliver biological agents for insect, weed, and plant disease control.